Use of composite SiO2 (62-68)-MgO + CaO (29-39) in ceramic protection mass injection machines in the iron notch and liquid slag hole in blast furnaces - Magnago, Roberto de Oliveira; Nogueira, Anderson Carvalho; da Silva, Paula Cipriano; de Souza, José Vitor Candido [UNESP]; dos Santos, Claudinei (Trans Tech Publications, 2017)
The article describes the use of protection ceramic composed of SiO2 (62-68)-MgO+CaO (29-39) in the frontal region of machines that inject refractory mass to stop pig iron running and liquid slag in blast furnaces. The new protection model (prototype) showed an annual saving of approximately R$ 32,000 compared to the compound previously used CaO-Al2O3-SiO2. It also presented lower toxicity, once it has in its morphology less amount of fiber. These fibers when inhaled cause damage to internal lungs tissues becoming harmful to health. Production rates remained, since in all the new ceramic protection samples that were tested the frontal part was preserved allowing the refractory mass to be injected in proper quantity and pressure for reconstitution of the hole length, which removes iron and slag from blast furnace. Therefore, this enables a larger internal volume in order to produce more. The protection models used were from the company Morganite-Brasil. The material morphology and crystallographic characterization were realized by Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD), respectively.
Keywords: Blast furnace; Ceramic protection; Pig iron; Silica